Magnetostratigraphy, age and depositional environment of the Lobo Formation, southwest New Mexico: implications for the Laramide orogeny in the southern Rocky Mountains - De los Santos, Marie G.; Lawton, Timothy F.; Copeland, Peter; Licht, Alexis; Hall, Stuart A. (Basin research, 2018)
The Lobo Formation of southwestern New Mexico consists of spatially variable continental successions attributed to the Laramide orogeny (80–40 Myr), although its age and provenance are virtually undocumented. This study combines sedimentological, magnetostratigraphical and geochronological data to infer the timing and origin of the Lobo Formation. Measured sections of Lobo strata at two locations, Capitol Dome in the Florida Mountains and in the Victorio Mountains, indicate significant differences in depositional environments and sediment provenance. At Capitol Dome, where Lobo strata were deposited above a syncline developed in Palaeozoic strata, deposition took place in fluvial, palustrine and marginal lacustrine settings, with alluvial‐fan deposits only at the top of the formation. Combined magnetostratigraphy and a young U–Pb detrital zircon age suggest deposition of the section at Capitol Dome from ~60 to 52 Ma. The Lobo Formation in the Victorio Mountains was deposited in alluvial‐fan and fluvial settings; the age of deposition is poorly bracketed between 66 ± 2 Ma, the weighted‐mean age of two young zircons, and middle Eocene (~40 Ma), the approximate age of overlying volcanic rocks. U–Pb zircon ages from sandstones at the Victorio and Capitol Dome localities indicate that different source rocks provided sediment to the Lobo Formation. Local Proterozoic basement (~1.47–1.45 Ga) dominated the source of the Lobo Formation in the Victorio Mountains, consistent with abundant granitic clasts that are present in the proximal facies there; a diverse range of grain ages suggest that recycled Lower Cretaceous strata provided the dominant source for Lobo Formation sediment at the Capitol Dome locality. The U–Pb data suggest that the depositional systems at the two sites were not connected. Contrasts in depositional setting and detrital zircon provenance indicate that the Palaeogene Lobo Formation in southwest New Mexico was deposited in an assemblage of local depositional settings, possibly in separate structural basins, as a consequence of Laramide tectonics in the region.